Characterization of [3H]CGP 12177 binding to beta-adrenergic receptors in intact eel hepatocytes - E. FABBRI; C. SELVA; T. W. MOON; CAPUZZO, Antonio (General and Comparative Endocrinology, 2001)
The aim of this study was to characterize [3H]CGP 12177 (CGP) binding to β-adrenergic receptors in isolated hepatocytes of the European eel (Anguilla anguilla), in which the involvement of cAMP in epinephrine-induced glucose release has been previously observed. Specific binding of CGP was saturable, reversible, and linear as a function of cell number. Analysis of binding data suggested a single class of binding sites, with a Kd of 1.31 nM and a number of approximately 7000 β-adrenergic receptors per cell. The potency order of specific inhibition of [3H]CGP binding was CGP > propranolol ≥ alprenolol ≫ butoxamine ≥ atenolol, while phentolamine and prazosin failed to significantly displace the tracer at concentrations up to 100 μM. The binding kinetics of CGP were closely related to its biological effect. In fact, the drug dose-dependently counteracted the enhancement of intracellular cAMP levels induced by epinephrine in isolated hepatocytes with a Kd of 1.06 nM. Moreover, it antagonized the hormone-induced stimulation of adenylyl cyclase activity in hepatic membranes as well as of glucose release from cells. These data clearly show that β-adrenergic receptors are coupled to the adenylyl cyclase/cAMP transduction pathway in eel liver. © 2001 Academic Press.